International Congress of Oral Implantologists.: June 2017, Krakow, Poland - Aravena, Pedro C (Journal of Oral Research, 2019)
Last June, the tenth European International Congress of Oral Implantologists (ICOI Europe Congress) was held in the beautiful city of Krakow, Poland, from June 8-11. This conference brought together more than 330 participants from all over the world, 18 lecturers, 23 scientific works, and 26 workshops in implantology.